Social and Economic Position of Wallachians and Albanians in Bosnia Under the Ottoman Rule - Mulić, Jusuf (Prilozi za orijentalnu filologiju, 2017)
The Ottomans found many groups of Wallachians and Albanians in all conquered South-Slavic countries, and in the Kingdom of Bosnia only in the feudal region of Herzegovina. The latter served in their military and economic system, especially for populating the parts of Bosnia which had been deserted by the indigenous population. This forced the followers of the Bosnian Church in the King.s territories in Herzegovina and the Catholic Church followers to flee from the Ottomans into adjacent Catholic countries, or the displacement of the indigenous population to Asia Minor upon the Ottoman occupation. Wallachian chiefs were included in the Ottoman timar-spahi system, and the Wallachian population in the military ranks according to the principle of voluntarism (martolosi), or the principle of legitimate army in the military ranks, or on Imperial orders in the auxiliary military ranks (gorges and mountain passages guards or derbendžije and falconers or dogandžije and dog guides, etc.). As remuneration for service in the spahi army, Wallachian chiefs were awarded proceeds from timars /feudal lands, property/ and čifluci /agrarian land/, and the Wallachian population who were martolosi, some tax relief or salaries (ulufedžije). The Wallachian population, from whose ranks the conscripts were recruited, paid the taxes which ensured them a more favourable economic and social position compared to the agricultural population. Those liabilities were defined by the so-called Wallachian custom or Wallachian law, which the Ottomans took over from the last Serb Despotate (Despot.s law on the Wallachians) and, with certain amendments and additions, they applied it to all former medieval South-Slavic countries. Laws were passed for particular vilejets (regions) and were applied to the whole sanjak (province) to which that particular vilajet belonged. Not all sanjaks used to have their Wallachin laws, so that those laws from the neighbouring sanjaks were applied to them. The Wallachian population carrying out the services of gorges and mountain passages guards, falconers and dog guides, used to pay taxes in accordance with all provisions of the Wallachian law, or only filuria, depending on the circumstances. The first application of the Wallachian custom, or the Wallachian law, i.e., the Despot.s law on Wallachians in the territory of the South-Slavic countries was on the Skoplje Border in 1455. The first written Ottoman Wallachian law was issued for the vilajet of Braničevo within the Vidinski sanjak and for the Smederevski sanjak between 1459 and 1467/1468, then for the Bosnian sanjak within which also was the vilajet of Hercegovina, in 1468/69, and the last one for the Smederevski sanjak in 1527/1528. Immediately after that the Wallachian law was abrogated, but due to the flight of Wallachians into enemy countries, who then lost their privileged social and economic position, its tacit restoration to power started as of the end of the fourth decade of the 16th century. With some changes in terms of integrating liabilities and their collection in cash, the Wallachian law remained in force until the very end of the Ottoman rule in Bosnia and other South-Slavic countries. In addition to the more favourable social and economic position, the Ottomans recognised local self-governance for the Wallachians in the form of Wallachian princedoms as of the beginning of the process of territorialization. In that way the Wallachians came to an even more favourable social position in comparison to the non-Wallachian population.